THE INFLUENCE OF MEDIA AND DIFFERENT STOCKING DENSITY ON THE POPULATION OF Daphnia Magna - Kurniawan, Agus; ', Nuraini; ', Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on April-May 2016 located at Jln. Kamboja No. 38, Simpang Baru, Panam, Pekanbaru. The purpose of this research to determine the population of Daphnia magna were cultured on different media and stocking density that generates the highest population. This research method used is an experimental method. The experimental design used was completely randomized design (CRD) with factorial design 2 factors which consisted of factors A: Media different that Poc Nasa 12 ml/l, Chicken Manure 12 g/l, Elephant Grass 12 g/l, Banana Stem 12 g/l and factor B: Solid different initial stocking 10 ind/l, 20 ind/l and 30 ind/l as many as 12 treatments, 3 repetitions so obtained 36 experimental units. Media and stocking density is very real (P<0,01) effect on the population Daphnia magna. The best treatment of Daphnia magna population during the 20 day study period generated by treatment of K12P30 (Chicken Manure 12g/l+ Stocking Density 30 ind/l) with an average value of 190. While the lowest for the treatment population N12P10 (Nasa 12 ml/l+Stocking Density 10 ind/l) with an overall average of 25 ind/l.Based on the analysis of the content of nutrients nitrogen (N) at the beginning and end of the study the culture medium Daphnia magna there are differences of each culture medium which is to Content Nitrogen (N) at the beginning of the study on media Chicken Manure 1,295 mg/l, Poc Nasa 0,622 mg/l, Elephant Grass 0,414 mg/l, and Banana Stem 0,518 mg/l. while the Content of Nitrogen (N) at the end of the study on Chicken Manure media 1.008 mg/l, Poc Nasa 1,915 mg/l, Elephant Grass 3,326 mg/l, and Banana Stem 0,907 mg/l. Water quality during the study showed a good range for growth of Daphnia magna is Temperatures range between 28,1 - 30,8 °C, DO ranged from 3,1 – 5,8 ppm and pH ranging from 7,1 – 8,5.Keywords : Media, Stocking density, Population, Daphnia magna